PUBLIC PERCEPTION IN IMPLEMENTING HEALTH PROTOCOLS AS PRECAUTION AGAINST COVID-19 ON HEALTH BELIEF MODEL THEORY - Idris, Meri Susanti; Mayang Sari Ayu (International Journal of Public Health Excellence (IJPHE), 2023)
Various efforts have been made to prevent Covid-19, but they have not made us utterly free from Covid-19 and can live normally again as before the pandemic. An integrated model is needed to improve public health behavior in preventing Covid-19 through increasing public awareness, health services, and appropriate legal regulations. Concurrent embedded mixed methods analysis was used, where quantitative and qualitative data were taken simultaneously and then analyzed to conclude. The Quantitative data measuring public health behavior is based on a health belief model questionnaire with a sample of 235 people. Qualitative data measuring health services and legal regulations were conducted using structured interview techniques with nine respondents as heads of Health service and sub-district leaders in Batubara Regency, selected by purposive sampling based on urban and rural areas. Correlation analysis between variables obtained correlation results with a weak relationship (r = 0.21-0.40), namely perceptions of vulnerability, severity, self-ability, instructions for action, and knowledge. Meanwhile, the perception of benefits and barriers has a moderate correlation (r=0.41-0.60). The results of multivariate correlation showed only four variables that have a correlation, namely perceptions of obstacles, benefits, instructions for action, and knowledge. Health services through preventive, promotive, and curative measures are classified as good, but the application of legal regulations still needs to be improved, so the results are not optimal. Efforts to improve legal regulations must consistently increase public awareness in preventing Covid-19 in Batubara Regency.